Prerequisites of Isopeptide Bond Formation in Microcystin Biosynthesis. (27th October 2017) - Meyer, Sabine; Mainz, Andi; Kehr, Jan‐Christoph; Süssmuth, Roderich D.; Dittmann, Elke
Abstract: The biosynthesis of the potent cyanobacterial hepatotoxin microcystin involves isopeptide bond formation through the carboxylic acid side chains ofd ‐glutamate and β‐methyld ‐aspartate. Analysis of the in vitro activation profiles of the two corresponding adenylation domains, McyE‐A and McyB‐A2, either in a didomain or a tridomain context with the cognate thiolation domain and the upstream condensation domain revealed that substrate activation of both domains strictly depended on the presence of the condensation domains. We further identified two key amino acids in the binding pockets of both adenylation domains that could serve as a bioinformatic signature of isopeptide bond‐forming modules incorporatingd ‐glutamate ord ‐aspartate. Our findings further contribute to the understanding of the multifaceted role of condensation domains in nonribosomal peptide synthetase assembly lines. Abstract : Isopeptide bond formation : In vitro characterization of nonribosomal peptide synthetase modules containing β‐Me‐d ‐Asp andd ‐Glu in the carboxylic side chains of the potent toxin microcystin provides new insight into isopeptide bond formation and the collaborative interaction of adenylation and condensation domains in substrate activation.